Overview of Cytostatic Drug Prescribing for Inpatient Cancer Patients at RSUD Tarakan July-December 2021 Period - Yetri Elisya; Nanang Kurnia Achmadi; Diki Kurniawan (Politeknik Kesehatan Kemenkes Jakarta II, 2022)
Chemotherapy, which uses cytostatic chemical medicine to kill or halt the growth of cancer cells, is one kind of treatment for cancer. In order to treat cancer, a variety of medication classes and delivery systems are used. The technique of study is retrospective and descriptive. Data collection for inpatients with cancer at RSUD Tarakan utilizing retrospective medical record data for the months of July through December 2021. This study aims to determine the demographic features of patients diagnosed with suspected cancer; the type of cancer most commonly suffered by patients; types, classes and combinations between cytotoxic drugs and combinations of therapeutic classes. Seventy patients were included in the study as research subjects who met the requirements. According to the study, there were 24 men (34.29 %) and 46 women patients. Twenty patients (or 28.57 %) are in the age range of 45 to 54. Breast cancer, which affected up to 16 people, was the most prevalent type of cancer. Alkalitor was the most commonly prescribed class of cytostatic medicines based on mechanism of action, with 54 prescriptions (32,53 %) written. Paclitaxel was the most commonly prescribed cytostatic medication, with 24 prescriptions (14,46 %). Fluorouracil + Irinotekan was the most commonly prescribed cytostatic medication combination, with 13 prescriptions (27.66 %). Dexamethasone was the most commonly prescribed combination of other therapeutic classes with cytostatic medicines, with 57 prescriptions (27,54 %).